Phytochemical Methods A Guide to Modern Techniques of Plant Analysis - Harborne, Jeffrey B (Chapman & Hall, 1998)
This long awaited third edition of Phytochemical Methods is, as its predecessors, a key tool for undergraduates, research workers in plant biochemistry, plant taxonomists and any researchers in related areas where the analysis of organic plant components is key to their investigations